In vitro virucidal activity of a commercial disinfectant against viruses of domestic animals and poultry - Sobhy, Nader M.; Quinonez-Munoz, Angie; Aboubakr, Hamada A.; Youssef, Christiana R. B.; Ojeda-Barría, Gonzalo; Mendoza-Fernández, Jonathan; Goyal, Sagar M. (Frontiers in Veterinary Science, 2024)
Outbreaks of viral diseases in animals are a cause of concern for animal welfare and economics of animal production. One way to disrupt the cycle of infection is by combating viruses in the environment and prohibiting them from being transmitted to a new host. Viral contamination of the environment can be reduced using well-tested and efficacious disinfectants. Duplalim is a commercially available disinfectant consisting of 12% glutaraldehyde and 10% quaternary ammonium compounds. We evaluated this disinfectant for its efficacy against several viruses in poultry (n=3), pigs (n=5), dogs (n=2), and cattle (n=4). In suspension tests, 1:100 dilution of Duplalim was found to inactivate more than 99% of these 14 viruses in 15 minutes or less. The titers of a majority of these viruses decreased by >99.99% in <60 min of contact time. In conclusion, the ingredient combination in Duplalim is very effective in inactivating common viruses of domestic animals and poultry.